Extraction of Eco-Friendly Natural Dyes from Pina Leaves and their Application on Wool Fabrics - J. Jalil, A.; Mahmood, S.; H. Abdul Rashid, A.; H. Nasir, S.; A. Ibrahim, S.; R. Ahmad, M. (International Journal of Engineering and Technology, 2019)
Natural dyes comprise of colorants that are obtained from animals or vegetable matters without any chemical processing. Natural dyes can substitute synthetic dye and promotes green technology initiatives in the field of textile dyeing. This study was carried out by extracting dyes from pineapple leaves (Ananas Comosus) using three stage mordanting methods using different mordants namely pre-mordanting, post-mordanting and simultaneous dyeing-mordanting. The mordants used were aluminium potassium sulphate, white vinegar and sodium chloride (NaCl). Wool fabrics were used for dyeing. The strength of colour and K/S values of the dyed fabrics were measured before and after washing. The colourfastness to washing, rubbing and light fastness of the fabrics were conducted to investigate the performance of the dye and mordants. The results indicate that the washing, rubbing and light fastness properties of dyed samples were between good to excellent grades.
Keywords: Ananas Comosus; Mordants; Natural Dye; Pina Leave; Wool.